βig-h3 promotes human osteosarcoma cells metastasis by interacting with integrin α2β1 and activating PI3K signaling pathway. - Yun-Shan Guo (Public Library of Science (PLoS), 2014)
Osteosarcoma, the most common primary bone tumor in children and young adolescents, is characterized by local invasion and distant metastasis. But the detailed mechanisms of osteosarcoma metastasis are not well known. In the present study, we found that βig-h3 promotes metastatic potential of human osteosarcoma cells in vitro and in vivo. Furthermore, βig-h3 co-localized with integrin α2β1 in osteosarcoma cells. But βig-h3 did not change integrin α2β1 expression in Saos-2 cells. Interaction of βig-h3 with integrin α2β1 mediates metastasis of human osteosarcoma cells. The second FAS1 domain of βig-h3 but not the first FAS1 domain, the third FAS1 domain or the fourth FAS1 domain mediates human osteosarcoma cells metastasis, which is the α2β1 integrin-interacting domain. We further demonstrated that PI3K/AKT signaling pathway is involved in βig-h3-induced human osteosarcoma cells metastasis process. Together, these results reveal βig-h3 enhances the metastasis potentials of human osteosarcoma cells via integrin α2β1-mediated PI3K/AKT signal pathways. The discovery of βig-h3-mediated pathway helps us to understand the mechanism of human osteosarcoma metastasis and provides evidence for the possibility that βig-h3 can be a potential therapeutic target for osteosarcoma treatment.